The immunosuppressive impact of PRRS virus on the immune response following anti - erysipelas vaccination in swine from various farms - Viorica Chiurciu; Costin C. Stoica; Maria Mioara Raduta; Catalin Tudoran; Lucia Diaconu; Ion Iacob (Medicamentul Veterinar)
PRRS virus, the etiologic agent of Porcine Reproductive and Respiratory Syndrome by immunosuppressive action can significantly affect the immune response after vaccination. It was intended the following of the immunological reaction induced by the Erysipelothrix rhusopathiae vaccination from pigs from intensive system and from households. The biological material studied was provided from clinically healthy pigs of different ages. The animals were from four different locations. Serological examinations were performed by blood sampling [gathered from the confluence of jugular vein] before and after the vaccination. The investigations were performed by ELISA method. In the industrial breeding system, seroprevalence of anti PRRS presented high levels, in contrast to the low level of postvaccinal E. rhusopathiae antibodies. In households the incidence of PRRS virus was low and the seroconversion after the vaccination was raised. The morphopathological and bacteriological examinations performed from the lesions in various organs [lungs, lymph nodes, liver, spleen and intestine] has revealed the presence of germ association, pathogenic or potentially pathogenic. The results point the link between the existence of PRRS virus in the swine populations and post-vaccinal response, its presence interfering significantly with the vaccination protocols efficacy.